Uncovering the nucleus candidate for NGC 253 - Gunthardt, Guillermo Ivan (2015)
NGC 253 is the nearest spiral galaxy with a nuclear starburst that becomes the best candidate for studying the relationship between starburst and active galactic nucleus activity. However, this central region is veiled by large amounts of dust, and it has been so far unclear which is the true dynamical nucleus to the point that there is no strong evidence that the galaxy harbors a supermassive black hole co-evolving with the starburst as was supposed earlier. Near-infrared (NIR) spectroscopy, especially NIR emission line analysis, could be advantageous in shedding light on the true nucleus identity. Using Flamingos-2 at Gemini South we have taken deep K-band spectra along the major axis of the central structure and through the brightest infrared source. In this work, we present evidence showing that the brightest NIR and mid-infrared source in the central region, already known as radio source TH7 and so far considered just a large stellar supercluster, in fact presents various symptoms of a genuine galactic nucleus. Therefore, it should be considered a valid nucleus candidate. Mentioning some distinctive aspects, it is the most massive compact infrared object in the central region, located at 2.″0 of the symmetry center of the galactic bar, as measured in the K-band emission. Moreover, our data indicate that this object is surrounded by a large circumnuclear stellar disk and it is also located at the rotation center of the large molecular gas disk of NGC 253. Furthermore, a kinematic residual appears in the H2 rotation curve with a sinusoidal shape consistent with an outflow centered in the candidate nucleus position. The maximum outflow velocity is located about 14 pc from TH7, which is consistent with the radius of a shell detected around the nucleus candidate, observed at 18.3 μm (Qa) and 12.8 μm ([Ne ii]) with T-ReCS. Also, the Brγ emission line profile shows a pronounced blueshift and this emission line also has the highest equivalent width at this position. All this evidence points to TH7 as the best candidate for the galactic nucleus of NGC 253.